PLCγ2 impacts microglia-related effectors revealing variants and pathways important in Alzheimer’s disease - Li, Ke; Ran, Beibei; Wang, Yu; Liu, Lulu; Li, Weidong (Frontiers in Cell and Developmental Biology, 2022)
Alzheimer’s disease (AD) is an irreversible neurodegenerative disease mainly characterized by memory loss and cognitive decline. The etiology of AD is complex and remains incompletely understood. In recent years, genome-wide association studies (GWAS) have increasingly highlighted the central role of microglia in AD pathology. As a trans-membrane receptor specifically present on the microglia in the central nervous system, phosphatidylinositol-specific phospholipase C gamma 2 (PLCγ2) plays an important role in neuroinflammation. GWAS data and corresponding pathological research have explored the effects of PLCG2 variants on amyloid burden and tau pathologies that underline AD. The link between PLCγ2 and other AD-related effectors in human and mouse microglia has also been established, placing PLCγ2 downstream of the triggering receptor expressed on myeloid cells 2 (TREM2), toll-like receptor 4 (TLR4), Bruton’s tyrosine kinase (BTK), and colony-stimulating factor 1 receptor (CSF1R). Because the research on PLCγ2’s role in AD is still in its early stages, few articles have been published, therefore in this paper, we integrate the relevant research published to date, review the structural features, expression patterns, and related pathways of PLCγ2, and summarize the recent studies on important PLCG2 variants related to AD. Furthermore, the possibility and challenge of using PLCγ2 to develop therapeutic drugs for AD are also discussed.